ÃœBERMENSCHâ€™S PHILOSOPHICAL CONCEPT AS SEEN THROUGH SUPERMANâ€™S CHARACTER IN ZACK SNYDERâ€™S â€œMAN OF STEELâ€ - Rr. Arielia Yustisiana (Universitas Katolik Widya Mandala Surabaya, 2024)
What people think about Superman is that he was not real. There was no one as strong as Superman in the world. However, some people believe that what matters about Superman is he cares about everyone in the universe without exception, without judgment. The article aims to elevate Supermanâ€™s values to human existence. The research focuses on the character of Clark Kent in Zack Snyderâ€™s two movies entitled Man of Steel. Clark initially used his powers covertly to help people and prevent or thwart disasters. He is valuable to humanâ€™s existence in the universe. The theory that is used to support to the analysis is Nietzscheâ€™s super human version, the UÌˆbermensch in English means Beyond-Man, Superman, Overman or Superhuman. It is the concept of Nietzscheâ€™s philosophy. Nietzscheâ€™s thought on human philosophy directs us to fully love the life and position humans as superhuman. The research design that is taken is qualitative research. There is one literary approach that meets the analysis, that is, archetypal approach. The finding of the research is that Clark Kent as the representation of UÌˆbermensch is a human that sees himself as a source of value. Human who has reached UÌˆbermensch is a person who always says â€œyesâ€ to everything and is ready to face challenges, who has an attitude of always affirming his life.